Normative Data for Bone Mass in Healthy Term Infants from Birth to 1 Year of Age - Sina Gallo; Catherine A. Vanstone; Hope A. Weiler (Journal of Osteoporosis)
For over 2 decades, dual-energy X-ray absorptiometry (DXA) has been the gold standard for estimating bone mineral density (BMD) and facture risk in adults. More recently DXA has been used to evaluate BMD in pediatrics. However, BMD is usually assessed against reference data for which none currently exists in infancy. A prospective study was conducted to assess bone mass of term infants (37 to 42 weeks of gestation), weight appropriate for gestational age, and born to healthy mothers. The group consisted of 33 boys and 26 girls recruited from the Winnipeg Health Sciences Center (Manitoba, Canada). Whole body (WB) as well as regional sites of the lumbar spine (LS 1–4) and femur was measured using DXA (QDR 4500A, Hologic Inc.) providing bone mineral content (BMC) for all sites and BMD for spine. During the year, WB BMC increased by 200% (76.0±14.2 versus 227.0±29.7 g), spine BMC by 130% (2.35±0.42 versus 5.37±1.02 g), and femur BMC by 190% (2.94±0.54 versus 8.50±1.84 g). Spine BMD increased by 14% (0.266±0.044 versus 0.304±0.044 g/cm2) during the year. This data, representing the accretion of bone mass during the first year of life, is based on a representative sample of infants and will aid in the interpretation of diagnostic DXA scans by researchers and health professionals.